2022
DOI: 10.3390/biom12040496
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Pulmonary Hypertension, from Pathogenesis to Diagnosis and Treatment

Abstract: Pulmonary hypertension (PH) is a fatal and untreatable disease, ultimately leading to right heart failure and eventually death. microRNAs are small, non-coding endogenous RNA molecules that can regulate gene expression and influence various biological processes. Changes in microRNA expression levels contribute to various cardiovascular disorders, and microRNAs have been shown to play a critical role in PH pathogenesis. In recent years, numerous studies have explored the role of microRNAs in PH, focusing on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Among the candidate miRNAs, eight were previously reported to play a crucial role in PH (Fig. 5 D) [ 5 , 14 ]. In the present study, miR-96-5p was the most significantly upregulated miRNA when circItgb5 was knocked down (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the candidate miRNAs, eight were previously reported to play a crucial role in PH (Fig. 5 D) [ 5 , 14 ]. In the present study, miR-96-5p was the most significantly upregulated miRNA when circItgb5 was knocked down (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical clustering based on significant fold change of miR expression among PAH group divulged miscellaneous miR population ( Figure 2 C). Intriguingly, none of these miRs have been previously associated with PAH pathogenicity [ 17 ]. Gene ontology (GO) for biological processes analysis of these miRs did not result in any significant over-represented GO terms.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some studies reported over 150 plasma-derived miRs [ 25 ] while others reported only a few [ 26 , 27 , 28 ] being dysregulated in PAH. Increasing evidence indicated more research analyzing the expression profiles of miRs and their signaling pathway in cells of the pulmonary vasculature, animal models of PAH, and PAH patients [ 17 ]. In rodent models of hypoxia-induced PAH, suppression of miR-204, miR-22, miR-30, and let-7f while up-regulation of miR-322 and miR-451 was observed [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reintroducing miR-204 in human pulmonary ECs and mouse models has been demonstrated to enhance hemodynamic parameters and reduce the proliferation of pulmonary vascular smooth muscle cells. MiR-21 is another miRNA that is relevant to PAH; it is upregulated in rat models, as well as in the pulmonary tissues of PAH patients [94]. Through the suppression of BMPR2, a protective factor in the pathophysiology of PAH, MiR-21 encourages the proliferation and survival of smooth muscle cells in the pulmonary vascular system [95].…”
Section: Aspects Of Vascular Biologymentioning
confidence: 99%